2003
DOI: 10.1093/pch/8.10.624
|View full text |Cite
|
Sign up to set email alerts
|

Infection control and paediatric tuberculosis: A practical guide for the practicing paediatrician

Abstract: Tuberculosis (TB) in children requires close attention to infection control to prevent transmission to other patients and health care workers. Although many children with TB are not infectious, appropriate airborne precautions must be maintained until conditions that increase the risk of transmission have been ruled out and accompanying adults, who may also be infectious, have been screened. Concurrent strategies to prevent TB transmission should be implemented, including administrative, engineering and person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…40 However, various studies (mainly carried out in the USA) reported a suboptimal compliance with these indications, without any substantial increase in nosocomial transmission. 41 44 …”
Section: Resultsmentioning
confidence: 99%
“…40 However, various studies (mainly carried out in the USA) reported a suboptimal compliance with these indications, without any substantial increase in nosocomial transmission. 41 44 …”
Section: Resultsmentioning
confidence: 99%
“…A large proportion of cases are concentrated in young adolescents, aged 10–14 years, who are more easily diagnosed and have an increased risk of exposure to TB [7] , [27] . In this group, the disease generally presents more like that of adults, is more often infectious, and is a major source of transmission [28] . In addition, adolescents are vulnerable and prone to challenges in follow-up and treatment adherence, reinforcing the importance of additional counseling for this age group [6] .…”
Section: Discussionmentioning
confidence: 99%
“…This aims to prevent transmission from cases to other patients or health care workers. The following means could help to ensure the protection of health care staff: Use of N95 mask by all staff on medical and TB isolation wards and in the HIV clinics [53]; HIV testing of all staff with reallocation of those testing positive to lower-risk positions; Annual Chest Xray screening for TB for all staff [24,54].…”
Section: Infection Controlmentioning
confidence: 99%